An overview of the landscape and approach for biofortification in Africa - Bouis, Howarth E.; Saltzman, A.; Ball, A.; Covic, Namukolo M.; Low, Jan W. (African Journal of Food, Agriculture, Nutrition and Development, 2017)
Mineral and vitamin deficiencies are a serious public health problem in Africa. The terrible consequences of these deficiencies are well known. Biofortification is the process of breeding nutrients into staple food crops. It is one cost-effective and sustainable agricultural investment that can help to reduce mineral and vitamin deficiencies, especially in the diets of the rural poor. This chapter discusses the key questions and impact pathway around which biofortification research has been oriented over the past 15 years, and sets the stage for subsequent chapters in this special issue on biofortification for the African Journal of Food, Agriculture, Nutrition, and Development.